Corporate Social Responsibility Makin Mesra Program PT. Bank Aceh Syariah Meulaboh Branch - Anisah, Anisah; Harmen, Hamdi; Rusdi, Rusdi; Jalis, Ivon; Mandavairo, Fitria (International Asia Of Law and Money Laundering, 2024)
This study aims to understand the impact of Corporate Social Responsibility (CSR) Program